The history of vaccines 3 - Rees, Anthony R. (Henry Stewart Talks, 2023)
Influenza: an ancient respiratory virus family, Influenza evolving structure, Antigen change: the cause of pandemics, Influenza vaccine, Immune response to vaccines, The Coronaviruses and their recent history, The CoV genome, SARS-CoV 2003 a short-lived epidemic, MERS-CoV 2012 attack, SARS-CoV-2 2019 pandemic, Vaccine development